(3aVGFd Gdjef hCgdgs - (3YHO GdQMef Hf Ydj Hf eMeO GdTjHGfqj GdRHjOj GdTGaYqj, hLjg GdOjf, GdeYQha H` GHf GdnqOrjnHY,J (B944 (3g` s
(3ChdgG (B:s
(3GeG HYO agPG LRA dWja jMJhi Ydi BjGJ ef cJGH Gddg GdYRjR fRdJ ai eYfi Gdjef Gdejehf hCMGOjK hQOJ Yf GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Ke eSLO egQed HfGUjI YQL Pdc JbOjQ GdYRjR s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B159s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B401 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B230 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs